The Role of mTOR in Amyotrophic Lateral Sclerosis - José Augusto Nogueira-Machado; Fabiana Rocha-Silva; Nathalia Augusta Gomes (Biomedicines)
Background: Amyotrophic lateral sclerosis (ALS) is a rare, progressive, and incurable disease characterized by muscle weakness and paralysis. Recent studies have explored a possible link between ALS pathophysiology and mTOR signaling. Recent reports have linked the accumulation of protein aggregates, dysfunctional mitochondria, and homeostasis to the development of ALS. mTOR plays a pivotal role in controlling autophagy and affecting energy metabolism, in addition to supporting neuronal growth, plasticity, and the balance between apoptosis and autophagy, all of which are important for homeostasis. Aim: This mini-review approaches the regulatory roles of mTOR signaling pathways, their interaction with other metabolic pathways, and their potential to modulate ALS progression. Significance: It discusses how these metabolic signaling pathways affect the neuromuscular junction, producing symptoms of muscle weakness and atrophy similar to those seen in patients with ALS. The discussion includes the concepts of neurocentric and peripheral and the possible connection between mTOR and neuromuscular dysfunction in ALS. Conclusions: It highlights the therapeutic potential of mTOR signaling and interconnections with other metabolic routes, making it a promising biomarker and therapeutic target for ALS.